Gravity inside the Earth and its characteristics - Sydykova Ж.К.; Erzhenbek Б.; Zheldybaeva Б.С.; Bitibaeva Ж.М.; Syrbaeva Ш.Ж.; Huangbai Е.; Zhukenov М.К.; Mukushev Б.А. (Recent Contributions to Physics, 2024)
At present, the parameters of the gravitational field of the Earth and the Solar System have been studied comprehensively. The physical regularities of gravitation of the Earth’s inner crust have not yet found a complete solution, although they have been studied for hundreds of years. This article investigates some physical characteristics of the interior of the Earth from the surface to the center. Based on the results of recent geophysical studies, a table has been compiled on the basis of experimental data to determine approximate values of some parameters of the gravitational field (gravity field strength (free fall acceleration), density of the Earth’s crust and its pressure) depending on the depth of the Earth. Theoretical models of density, pressure and acceleration of the Earth’s crust gravity depending on its depth were developed. The theoretical models were built using a mathematical method - the linear regression method. Comparisons were made between the equations describing these models and experimental data. These scientific results were analyzed and conclusions were drawn on the dynamics of change of parameters depending on depth, characterizing the gravitational field inside the Earth. The Mathcad 15 application software package was used in the search for solutions to mathematical models of the gravity characteristics of the Earth’s crust. Theoretical and experimental graphs describing the dependence of the Earth density, pressure and acceleration of gravity on depth were created with the help of Mathcad 15 package.